Interdisciplinary care clinics in chronic kidney disease. Issue 1 (December 2015) - Johns, Tanya; Yee, Jerry; Smith-Jules, Terrian; Campbell, Ruth; Bauer, Carolyn
Abstract The burden of chronic kidney disease (CKD) is substantial, and is associated with high hospitalization rates, premature deaths, and considerable health care costs. These factors provide strong rationale for quality improvement initiatives in CKD care. The interdisciplinary care clinic (IDC) has emerged as one solution to improving CKD care. The IDC team may include other physicians, advanced practice providers, nurses, dietitians, pharmacists, and social workers—all working together to provide effective care to patients with chronic kidney disease. Studies suggest that IDCs may improve patient education and preparedness prior to kidney failure, both of which have been associated with improved health outcomes. Interdisciplinary care may also delay the progression to end-stage renal disease and reduce mortality. While most studies suggest that IDC services are likely cost-effective, financing IDCs is challenging and many insurance providers do not pay for all of the services. There are also no robust long-term studies demonstrating the cost-effectiveness of IDCs. This review discusses IDC models and its potential impact on CKD care as well as some of the challenges that may be associated with implementing these clinics.